Insights Into Limnothrix sp. Metabolism Based on Comparative Genomics - Lima, Alex Ranieri Jerônimo; Siqueira, Andrei Santos; Vasconcelos, Janaina Mota de; Pereira, James Siqueira; Azevedo, Juliana Simão Nina de; Moraes, Pablo Henrique Gonçalves; Aguiar, Délia Cristina Figueira; de Lima, Clayton Pereira Silva; Vianez-Júnior, João Lídio Silva Gonçalves; Nunes, Márcio Roberto Teixeira; Xavier, Luciana Pereira; Dall’Agnol, Leonardo Teixeira; et al. (Frontiers in Microbiology, 2018)
Currently only four genome sequences for Limnothrix spp. are publicly available, and information on the genetic properties of cyanobacteria belonging to this genus is limited. In this study, we report the draft genome of Limnothrix sp. CACIAM 69d, isolated from the reservoir of a hydroelectric dam located in the Amazon ecosystem, from where cyanobacterial genomic data are still scarce. Comparative genomic analysis of Limnothrix revealed the presence of key enzymes in the cyanobacterial central carbon metabolism and how it is well equipped for environmental sulfur and nitrogen acquisition. Additionally, this work covered the analysis of Limnothrix CRISPR-Cas systems, pathways related to biosynthesis of secondary metabolites and assembly of extracellular polymeric substances and their exportation. A trans-AT PKS gene cluster was identified in two strains, possibly related to the novel toxin Limnothrixin biosynthesis. Overall, the draft genome of Limnothrix sp. CACIAM 69d adds new data to the small Limnothrix genome library and contributes to a growing representativeness of cyanobacterial genomes from the Amazon region. The comparative genomic analysis of Limnothrix made it possible to highlight unique genes for each strain and understand the overall features of their metabolism.